Blocking LINGO-1 as a Therapy to Promote CNS Repair: From Concept to the Clinic - Mi, Sha; Blake Pepinsky, R.; Cadavid, Diego (CNS drugs, 2013)
LINGO-1 is a leucine-rich repeat and Ig domain-containing, Nogo receptor interacting protein, selectively expressed in the CNS on both oligodendrocytes and neurons. Its expression is developmentally regulated, and is upregulated in CNS diseases and injury. In animal models, LINGO-1 expression is upregulated in rat spinal cord injury, experimental autoimmune encephalomyelitis, 6-hydroxydopamine neurotoxic lesions and glaucoma models. In humans, LINGO-1 expression is increased in oligodendrocyte progenitor cells from demyelinated white matter of multiple sclerosis post-mortem samples, and in dopaminergic neurons from Parkinson’s disease brains. LINGO-1 negatively regulates oligodendrocyte differentiation and myelination, neuronal survival and axonal regeneration by activating ras homolog gene family member A (RhoA) and inhibiting protein kinase B (Akt) phosphorylation signalling pathways. Across diverse animal CNS disease models, targeted LINGO-1 inhibition promotes neuron and oligodendrocyte survival, axon regeneration, oligodendrocyte differentiation, remyelination and functional recovery. The targeted inhibition of LINGO-1 function presents a novel therapeutic approach for the treatment of CNS diseases.